Diagnosis And Clinical Course of Chronic Generalised Periodontitis in Connective Tissue Dysplasia (Eurasian Medical Research Periodical, 2022)
The present study focuses on 104 patients with differentiated connective tissue dysplasia (DCTD) (Marfan syndrome) and undifferentiated connective tissue dysplasia (UDCTD). General clinical investigations - questioning, physical examination, instrumental, biochemical, and chemoluminescent procedures were used.